NILAI-NILAI MASLAHAH DALAM HUKUM POTONG TANGAN: ANALISIS KRITIS PERSPEKTIF HADIS AHKAM - Abdul Somad, Bukhori (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
The Values of Mashlahah in Punishment of Hand Amputation: Critical Analysis of Hadith Ahkâm. Certaingroups of legal exponents advocating human rights proclaim that Islam is sadistic, inhumane, and anti humanrights religion. The claim is considerably in contrast to the quantum of human benefits which Islamic law contains.Islam, in fact, appreciates and stresses an importance of human right. There is no doubt that Islam exactly savesthe aggressived person through punishment of cutting off theif’s hand, when its criterion has been complete.Such punishment is instructive and has wary effect on those who steal property by illegal means. Hence, Islamactually reduces criminal activities in our daily life. Islam has definite rule that regulates a punishment for allthieves. Its regulation is applied in accordance with the legal criterion laid down for hand amputation, however,they will be free from the punishment if the property owner forgives them at all. This indicates that Islam reallyapreciates human values as well as loves peace and order in the public interest.